Empirical study on flow experience in China tourism e-commerce market - Jianling Wang; Meng Wang; Junyan Wu (Journal of Industrial Engineering and Management (JIEM), 2015)
Purpose: While tourism e-commerce develops rapidly in China, these channels are truly new to both web providers and web consumers, understanding the nature of these media attaches greater importance. This study investigates the mediation effects of flow experience on the relationship between motivation and behavior intention in tourism e-commerce. Design/methodology/approach: Based on the technology acceptance model, an empirical study is designed to test this relationship. We estimated the measurement model with 13 manifest indicators and 4 latent constructs by CFA to assess the reliability and validity of the construct measures, then tested hypotheses by OLS regression and a formal three-step mediation procedure. Findings: Overall, the results reveal that trust is incorporated in motivation and play it's role together with other motivations; telepresence and concentration are confirmed in flow experience, and both partially mediated the relationship. Research limitations/implications: This study demonstrates that to improve consumers' usage adoption, marketers should pay much attention to not only consumers' motivation but also the areas such as flow experience. Originality/value: this study takes flow experience as a new perspective to explore China tourism e-commerce, estimates its measurement and tests its roles between motivation and behavior intention.
Keywords: 650; tourism e-commerce; flow experience; consumer motivation; mediation